The Significance of the Scientific Heritage of Eastern Thinkers in the Formation of Patriotic Feelings in Primary Class Students - qizi, Sattorova Nazira Safar (European Journal of Life Safety and Stability (2660-9630), 2023)
The article discusses the importance of the scientific heritage of Eastern thinkers, including Abu Nasr Farabi, Abu Raikhan Beruni, Abu Ali Ibn Sina, Al-Khwarazmi, in the formation of patriotic feelings in elementary school students.